Effects of pulmonary rehabilitation on immune mediators detected in the saliva of people with COPD - Dias, Joana Pinto (2019)
Background: Chronic obstructive pulmonary disease (COPD) is the third leading cause of death in the world. It is characterised by persistent and progressive airway obstruction associated with a chronic inflammatory response in the airways and lungs. These patients have altered levels of pro / anti-inflammatory cytokines and of secretory IgA (SIgA). Pulmonary rehabilitation (PR) is the most effective therapeutic intervention in improving the daily symptoms, exercise tolerance, functionality, muscle strength and quality of life of people with COPD, but its impact of on the levels of inflammatory mediators and SIgA is not consensual. Aim: To compare the levels of inflammatory mediators (TNF-α, IL-6, IL-8 and IL-10) and SIgA in saliva samples from people with COPD and from healthy people. To evaluate the impact of PR on these mediators and SIgA and correlate their levels with clinical data. Methods: People with COPD were recruited from primary health care and enrolled in a community PR programme twice a week during three months. Sociodemographic (age, sex), anthropometric (height, weight) and clinical data (lung function- FEV1pp, six minute walking test- 6MWT, quadriceps and handgrip muscle strength, functionality- 1 min sit-to-stand) were collected three months before, immediately before, immediately after and three months after PR. Saliva samples of people with COPD were collected every month and stored at -80 ° C. Healthy people were recruited from senior academies and surrounding community, and evaluated once. Inflammatory mediators and SIgA were quantified by ELISA. Results: Twenty people with COPD (n=14, 70% male; 71 [67.3-76] years; FEV1pp= 48.2±16.4) and eleven healthy people (n=6, 54.5% male; 73 [68-74] years; FEV1pp=109.6±27.6) participated in the study. No significant differences were found in the levels of analysed cytokines and SIgA between patients with COPD and healthy people. IL-10 was not detected in most samples. In the last PR session, a significant increase in IL-6 was observed. It was observed a trend towards an increase of SIgA during PR. Before PR we found a significant positive correlation between TNF-α and quadriceps muscle strength in responder patients (p=0.0026; r=0.9580) and between IL-6 and 6MWT in all patients (p=0.0191; r=0.6222). After PR a significant positive correlation between IL-6 and quadriceps muscle strength (p=0.0463; r=0.5269) was observed. Significant correlations were found (0.0025≤ p ≥ 0.0438; -0.8009 ≤ r ≥ 0.9539) between SIgA and FEV1pp, handgrip strength, 1 minute STS, 6MWT and quadriceps muscle strength at different times of the study. Conclusion: This study suggest that PR leads to a significant increase in IL-6 and to a variation of SIgA levels, although not significant. Furthermore, IL-6, TNF-α, but mostly SIgA seem to correlate with clinical parameters of people with COPD. Further studies are needed to confirm some trends observed and to increase our knowledge on the variation of the inflammatory response during PR.